Can you use community policing for counter terrorism? Evidence from NSW, Australia. (3rd May 2016) - Dunn, Kevin Mark; Atie, Rosalie; Kennedy, Michael; Ali, Jan A.; O'Reilly, John; Rogerson, Lindsay
Abstract : A contested question in the international policing literature is whether it is possible to undertake effective anti-terrorism community policing. The NSW Police Force's Counter Radicalisation Strategy involved a community engagement initiative that used community liaison officers, mostly working with Sydney Muslim communities. This study reviews the success of this initiative, drawing on data from a survey of Sydney Muslims. The community engagement initiative was found to have direct contact with the community, it was public, and it involved aspects of partnership and relations of depth. For these reasons, the initiative was within the community policing paradigm. There was strong community awareness of the programme, and a majority saw it as successful. There remained pockets of community suspicion and critique, which require attention. The respondents recommended an enhancement of the community policing aspects: more (and wider) contact, visibility and partnership. The findings affirm the utility of community policing for counter-terror work.